Pengaruh Soda Ash dan Media Filter Sintetis Terhadap Kekeruhan dan pH Air - Khair, Abdul; Noraida, Noraida (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari Banjarmasin, 2023)
Water treatment methods are very diverse, including neutralization methods and filtration methods. In this study, the material used in the neutralization process is soda ash, while filtration uses synthetic filter media. This method is used to improve the quality of clean water in households on turbidity and pH parameters. The purpose of the study was to determine the effect of the addition of soda ash and filtration using synthetic filter media on turbidity and pH of Anjir Pasar river water. This type of research is an experiment with pretest-postest design with control group. Variations of synthetic filter media used are without filter media, catridge foam, cloth, cotton, and a combination of filter media types. Turbidity before treatment was 42 NTU with a pH of 3.8. After neutralization using 10 grams of soda ash, the pH of the river water became 7.5. Meanwhile, the turbidity decreased to 36.55 NTU, 18.26 NTU, 3.89 NTU, 10.75 NTU, and 7.9 NTU after filtration with a media thickness of 60 cm with a turbidity reduction percentage of 13%, 57%, 91%, 74%, and 84%. The results of statistical analysis showed that there were differences in each type of synthetic filter media on the decrease in turbidity level and there were no differences in each type of synthetic filter media on the pH quality of Anjir Pasar river water.